Computed CH Acidity of Biaryl Compounds and Their Deprotonative Metalation by Using a Mixed Lithium/Zinc‐TMP Base1. Issue 24 (12th April 2013) - Kadiyala, Raghu Ram; Tilly, David; Nagaradja, Elisabeth; Roisnel, Thierry; Matulis, Vadim E.; Ivashkevich, Oleg A.; Halauko, Yury S.; Chevallier, Floris; Gros, Philippe C.; Mongin, Florence
Abstract With the aim of synthesizing biaryl compounds, several aromatic iodides were prepared by the deprotonative metalation of methoxybenzenes, 3‐substituted naphthalenes, isoquinoline, and methoxypyridines by using a mixed lithium/zinc‐TMP (TMP=2, 2, 6, 6‐tetramethylpiperidino) base and subsequent iodolysis. The halides thus obtained, as well as commercial compounds, were cross‐coupled under palladium catalysis (e.g., Suzuki coupling with 2, 4‐dimethoxy‐5‐pyrimidylboronic acid) to afford various representative biaryl compounds. Deprotometalation of the latter compounds was performed by using the lithium/zinc‐TMP base and evaluated by subsequent iodolysis. The outcome of these reactions has been discussed in light of the CH acidities of these substrates, as determined in THF solution by using the DFT B3LYP method. Except for in the presence of decidedly lower pKa values, the regioselectivities of the deprotometalation reactions tend to be governed by nearby coordinating atoms rather than by site acidities. In particular, azine and diazine nitrogen atoms have been shown to be efficient in inducing the reactions with the lithium/zinc‐TMP base at adjacent sites (e.g., by using 1‐(2‐methoxyphenyl)isoquinoline, 4‐(2, 5‐dimethoxyphenyl)‐3‐methoxypyridine, or 5‐(2, 5‐dimethoxyphenyl)‐2, 4‐dimethoxypyrimidine as the substrate), a behavior that has already been observed upon treatment with lithium amides under kinetic conditions. Finally, the iodinated biaryl derivatives were involved in palladium‐catalyzed reactions.